2017
DOI: 10.1016/j.scr.2017.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Hoxa9 and EGFP reporter expression in human Embryonic Stem Cells (hESC) as useful tools for studying human development

Abstract: HoxA9 is an evolutionarily conserved homeobox gene implicated in embryo development. To study the roles of Hoxa9 during human development we generated a transgenic H9 (hESC) line that overexpresses HoxA9 and the Enhanced Green Fluorescent Protein (EGFP), and a control H9 with a stable expression of the EGFP. The resulting H9-HoxA9-EGFP and H9-EGFP cell lines allow an efficient visualization of hESCs by fluorescent microscopy, quantification by flow cytometry and cell differentiation tracking. Both transgenic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…We differentiated pluripotent human ESC H9-GFP 18 expressing OCT4 and SOX2 into mDA (Fig. 1 a), using a reported floor-plate protocol 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We differentiated pluripotent human ESC H9-GFP 18 expressing OCT4 and SOX2 into mDA (Fig. 1 a), using a reported floor-plate protocol 12 .…”
Section: Resultsmentioning
confidence: 99%
“…H9 human embryonic stem cells (WA09) of female origin were purchased from WiCell (Madison, WI, USA), transduced with lentiviral vectors to express GFP as described 18 and cultured until 75% confluency. These GFP-expressing cells are useful for transplantation studies 13 and behave as its parental H9 hESC.…”
Section: Methodsmentioning
confidence: 99%
“…25 HOXB13-AS1 is a 564 nucleotide-lncRNA and situates in the homeobox (HOX) gene locus on chromosome 17, which has been identified to function critical roles in embryo development and numerous cellular processes. [26][27][28][29] A substantial body of scientific evidence reported that aberrations in HOX gene expression associated with many different types of malignancies. Recently, certain kinds of lncRNAs have been reported to be located on HOX gene clusters, including HOXB13-AS1.…”
mentioning
confidence: 99%
“…Enhanced Green fluorescent protein (EGFP) expressing hESCs were employed [19]. We first corroborated the expression of pluripotency markers in H9 wild-type hESCS by detecting OCT4, SOX2, NANOG, and SSEA4 (Figure S1A).…”
Section: Dopaminergic Neuron Differentiationmentioning
confidence: 87%